Awareness, Knowledge and Attitudes Towards Safe Antibiotic Use among Outpatient Visitors at a Teaching Hospital in Malaysia - Khaleeda Zaki; Mohd. Azri Abd. Jalil; Shidqiyyah Abdul-Hamid (Asian Journal of Medicine & Health Sciences, 2024)
Introduction: Antimicrobial resistance has emerged as a significant issue largely due to the misuse of antibiotics in treating bacterial infections since their introduction. Misuse of antibiotics includes failure to finish the full course and prematurely stopping their antibiotic treatment after symptoms improve. Although antibiotics cannot be self-prescribed in Malaysia, misuse still occurs among consumers. Purpose: This study aimed to assess the level of awareness, knowledge and attitude (AKA) on safe antibiotic use among outpatient visitors of a teaching hospital in Pahang, Malaysia. The association between sociodemographic background and AKA score was also explored to identify the knowledge gap within various backgrounds. Methods: A total of 206 participants were recruited for this study. The participants were approached at several outpatient departments in a teaching hospital using convenient sampling from May until June 2022 and completed a set of validated questionnaires. The data were analysed using SPSS. Results: Only 35.4% of participants obtained a high score in knowledge, while the majority scored moderately. Among the 206 participants, 51.0% had poor awareness of safe antibiotic use. More than half of the participants (63.1%) exhibited a positive attitude towards antibiotic consumption. Education level and medical background were shown to be statistically significant to AKA scores. Conclusion: This study highlights that despite moderate knowledge and poor awareness of safe antibiotic use among hospital attendees, a positive attitude towards antibiotics was observed. It is essential to implement public educational campaigns that address knowledge gaps and misconceptions to improve antibiotic safety among the population.